Limb Amputation after Multiple Treatments of Tenosynovial Giant Cell Tumour: Series of 4 Dutch Cases - Monique J. L. Mastboom; Floortje G. M. Verspoor; Hans Gelderblom; Michiel A. J. van de Sande (Case Reports in Orthopedics)
In Tenosynovial Giant Cell Tumours (TGCT), previously named Pigmented Villonodular Synovitis (PVNS), a distinction is made between a single nodule (localized-type) and multiple nodules (diffuse-type). Diffuse-type is considered locally aggressive. Onset and extermination of this orphan disease remain unclear. Surgical resection is the most commonly performed treatment. Unfortunately, recurrences often occur (up to 92%), necessitating reoperations and adjuvant treatments. Once all treatments fail or if severe complications occur, limb amputation may become unavoidable. We describe four cases of above-knee amputation after TGCT diagnosis.